Examining How Fact-checking Hubs Counter Information Disorder in Africa - Aliagan, Isiaka Zubair; Daranijo, Habeeb Opeyemi (Komunikator, 2025)
As fake news, misinformation, and communication disorders continue to raise societal concerns, several countermeasures are emerging to combat this growing challenge. This study examines the role of social media in the spread of information disorder in Africa and evaluates how effectively three prominent fact-checking websites—FactCheckHub, Dubawa, and Africa Check—are addressing this communication crisis. Using a content analysis methodology, the research identifies common types of misinformation circulating on Nigerian social media, analyzes existing fact-checking techniques, and assesses the contributions of the selected platforms in mitigating information disorder. Drawing on academic frameworks related to misinformation, disinformation, and verification, the study explores how social media facilitates the spread of false narratives and the societal consequences that ensue. It contributes to broader discussions on media literacy, information integrity, and the cultivation of an informed society in the digital age by providing insights into the dynamics of disinformation in Nigeria and the critical role of fact-checking initiatives in addressing it.